Teori Kuantifikasi Fuzi II Sebagai Alat Analisis Faktor-Faktor Kepuasan Konsumen Terhadap Swalayan: Kasus di Swalayan Indogrosir dan Alfa Yogyakarta - Budi Astuti; Sharly Putri (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Every company puts consumers’ satisfaction as the main priority in service to win the competition among similar companies. The use of Fuzzy Quantification II for evaluating the costumers’ satisfaction of two self-service supermarkets, namely Alfa and Indogrosir, had been done. Although both Indogrosir and Alfa have the same characteristic as supermarkets, they differ in the company policies and each has their own superiorities. The satisfaction level which are formed by several qualitative data will be transformed into numerical one. These two supermarkets are treated as an External Standard Variable ( y ) to become the objective function of purpose. There were 13 factors including the varieties and the quality of goods indicated as Parameter Variable which influence the satisfaction level. The results show that the varieties of goods are the most dominant factor for the costumers’ satisfaction. Futhermore, it shows that the satisfaction level for Alfa Supermarket is 0.69 and for Indogrosir is 0.60. Keywords: consumers’ satisfaction, fuzzy quantification, external standard variable.